Fusarium ramigenum, a novel human opportunist in a patient with common variable immunodeficiency and cellular immune defects: case report. Issue 1 (December 2016) - Moroti, Ruxandra; Gheorghita, Valeriu; Al-Hatmi, Abdullah; de Hoog, G.; Meis, Jacques; Netea, Mihai
Abstract Background Fusarium species are ubiquitous environmental fungi that occasionally provoke serious invasive infections in immunocompromised hosts. AmongFusarium species, Fusarium ramigenum, belonging to theFusarium fujikuroi species complex, has thus far never been found to cause human infections. Here we describe the first case of invasive fusariosis caused byFusarium ramigenum in a human and also identify immunological deficiencies that most likely contributed to invasiveness. Case presentation A 32-year-old Caucasian male with a seemingly insignificant medical history of mild respiratory illness during the preceding two years, developed invasive pulmonary fusariosis. Detailed immunological assessment revealed the presence of common variable immunodeficiency, complicated by a severe impairment of the capacity of T-cells to produce both gamma-interferon and interleukin-17. In-depth microbiological assessment identified the novel human opportunistic pathogenFusarium ramigenum as cause of the infection. Conclusion This report demonstrated that an opportunistic invasive fungal infection may indicate an underlying cellular immune impairment of the host. The unexpected invasive infection withFusarium ramigenum in this case unmasked a complex combined humoral and cellular immunological deficiency.